Salivary cortisol concentrations in institutionalized and non-institutionalized elderly people - Tânia Adas Saliba; Ana Carolina Bernardes Machado; Suzely Adas Saliba Moimaz; Nemre Adas Saliba (Editorial Ciencias Médicas, 2018)
Introduction: due to the limitations inherent to the process of aging, institutionalization is a reality which may have an impact on the physical and psychological health status of elderly people. Objectives: determine salivary cortisol concentrations in institutionalized and non-institutionalized elderly people, and verify variables such as oral health and physical dependence. Methods: a descriptive analytical cross-sectional study was conducted of a sample of 80 individuals, of whom 45 were institutionalized and 35 non-institutionalized. Oral clinical examination was performed to evaluate the use of and need for dental prostheses in the upper and lower arches. Saliva was collected to determine the concentration of cortisol, a biological marker of stress levels. Results: most of the sample were totally edentulous elderly people: 84.44 % in the institutionalized group and 71.43 % in the non-institutionalized group. A lower rate of prosthesis use was found in the institutionalized sample than in the non-institutionalized sample (p= 0.0013). Analysis of salivary cortisol concentrations revealed significant differences between the groups, with higher values in the institutionalized group (p= 0.0397). Higher salivary cortisol concentrations were found among individuals with prosthetic needs, the difference being statistically significant (p= 0.0454). Conclusions: institutionalized elderly people had higher salivary cortisol concentrations, greater prosthetic needs, and were more care dependent than the non-institutionalized group.